Cultural Symbolism of Balinese Islamic Society (Ethnographic Study in Pagayaman Village, Singaraja, Bali) - Amelia Safitri; Annisa Nadzirani Cahyarti; Nyoman Hidayat Ar-Rumy; Abd. Halim (Quality : Journal Of Education, Arabic And Islamic Studies, 2026)
This study aims to examine the cultural symbols that have developed within the Pagayaman Muslim community in Singaraja, Bali, and to explore their meaning and role in maintaining Islamic identity while building harmonious social relations with the surrounding community. This study uses a descriptive qualitative approach with an ethnographic analytical framework. Data collection was conducted through a literature review of relevant academic sources and in-depth interviews with key informants selected purposively based on their involvement and understanding of the cultural practices of the Pagayaman community. The results show that the cultural symbolism of the Pagayaman Muslim community is adaptive and deeply rooted in the community's historical experiences. The meaning of religious symbols, the spatial arrangement of settlements, social interaction patterns, and the implementation of communal traditions reflect this community's ability to maintain its Muslim identity amidst the dominance of Balinese culture. These findings confirm that symbolic diversity plays a crucial role in maintaining cultural sustainability, strengthening social cohesion, and building harmony between groups in a pluralistic society.